EFFECTIVENESS OF THE ROLE OF THE HOSPITAL BLU SUPERVISORY BOARD DURING THE COVID-19 PANDEMIC - Harjowiryono, Marwanto; Siallagan, Windraty Ariane (Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
The Covid-19 pandemic has significantly impacted the performance of Public Service Agencies (BLU), particularly hospital BLUs, contributing to the global economic crisis. This study examines the effectiveness of Hospital BLU Supervisory Board roles during the Covid-19 pandemic and their impact on hospital performance. Using a mixed-method approach, this research analyzed data from 208 respondents (134 supervisory board members and 74 BLU managers) through Likert-scale questionnaires and conducted in-depth interviews with 8 supervisory board members. Results indicate that the role of the Supervisory Board during the Covid-19 pandemic experienced increased intensity and a shift in focus. However, uneven understanding of existing governance necessitates routine activities for improving the Supervisory Board's role, including redesigning the appointment process. The study found that board effectiveness was influenced by member competency, governance understanding, communication quality, and collaborative leadership development.